The depressor mandible muscle in anurans - Manzano, Adriana Silvina (2003)
It is well known that the diversity in anuran cranial structures is large, observed in the variation of the bone structure and associated muscles. The depresso mandibulae is the jaw muscle that opens the mouth and was considered by many authors useful in delimiting anuran groups. However, there is still much controversy on the value of the m. depressor mandibulae as a relationship-indicating character. The goal of this project is to explore the morphological diversity of the depressor mandibulae muscle among different families of Anura. Specimens including 60 genera of 17 families of Anura were dissected, using traditional techniques of macroanatomy. Fifteen morphological groups can be distinguished within the anuran species analyzed. The insertion point demonstrates little variation. The overall pattern of the origin is also quite stable, with some exceptions. The great diversity in shape of the m. depressor mandibulae correlates with the plethora of patterns already mentioned for cranial morphology in anurans. However, it is difficult to asign a specific morphology to a given higher taxon. We also found no evidence that variations in the m. depressor mandibulae are associated with particular habits.